Scoping AI governance: A smarter tool kit for beneficial applications - Maroussia Lévesque (Centre for International Governance Innovation (CIGI), 2021)
Artificial intelligence (AI) systems can be used to promote equality and non-discrimination, but without the right AI governance strategies, they can have the opposite effect. This paper aims to provide policy makers with the tools they need to build beneficial AI systems. Harmful biases in AI systems often disproportionately affect racialized, low-income and minority groups. For example, algorithms that over- or underestimate scores create false-positive and false-negative results that can perpetuate systemic discrimination. Policy makers can address these concerns through interventions and regulations that promote AI fairness.
Keywords: 330